Поглиблений ексергетичний аналіз теплового насоса як елемента системи теплозабезпечення будинку з урахуванням сезонних коливань режимів роботи - Волощук, Володимир Анатолійович (НТУ "ХПІ", 2017)
В роботі наведені результати поглибленого ексергетичного аналізу теплового насосу на стічних водах, призначеного для теплозабезпечення будівлі з урахуванням сезонних коливань потреб енергії та температури низькопотенційного джерела. Показано, що у прийнятих умовах дійсне зниження деструкції ексергії у тепловому насосі можливе за рахунок зменшення необоротностей при передачі теплоти у випарнику та конденсаторі – тобто при допомозі зниження температурного напору у цих теплообмінниках.

In contrast to conventional exergy-based methods, advanced exergetic analyses can evaluate exergy destructions due to interactions among components of the energy-conversion system and the real potential for improving system components. Application of a detailed advanced exergetic analysison a wastewater source heat pump providing space heating in variable operation modes is proposed in the work. In order to determine thermodynamic parameters of the refrigeration vapor compresion cycle a special simulation model was used. The so-called thermodynamic-cycle-based approach was applied to split the exergy destruction within each component of a heat pump into unavoidable, avoidable, endogenous and exogenous parts. It is shown that in the investigated system only about 50 % of the total seasonal destructions in components of the heat pump can be avoided. About 40 % of this avoidable thermodynamic inefficiency is caused by interactions among components. According to the results received, in order to improve the thermodynamic performance of the analyzed heat pump the evaporator should be improved first and the condenser second. The compressor has very low potential for the heat pump improvement and the throttling valve has no potential for this purpose. Based on the applied advanced exergetic analysis it is possible to receive more precise and useful information for better understanding and improving the design and operation of the analysed heat pump.
Advanced exergetic analysis of a heat pump providing space heating taking into account seasonal variations of operation modes
Keywords: стічні води; потреби енергії; необоротність; випарник; конденсатор